Modulation of intrinsic inhibitory checkpoints using nano‐carriers to unleash NK cell activity - Biber, Guy; Sabag, Batel; Raiff, Anat; Ben‐Shmuel, Aviad; Puthenveetil, Abhishek; Benichou, Jennifer I C; Jubany, Tammir; Levy, Moria; Killner, Shiran; Barda‐Saad, Mira (EMBO molecular medicine, 2022)
Natural killer (NK) cells provide a powerful weapon mediating immune defense against viral infections, tumor growth, and metastatic spread. NK cells demonstrate great potential for cancer immunotherapy; they can rapidly and directly kill cancer cells in the absence of MHC‐dependent antigen presentation and can initiate a robust immune response in the tumor microenvironment (TME). Nevertheless, current NK cell‐based immunotherapies have several drawbacks, such as the requirement for ex vivo expansion of modified NK cells, and low transduction efficiency. Furthermore, to date, no clinical trial has demonstrated a significant benefit for NK‐based therapies in patients with advanced solid tumors, mainly due to the suppressive TME. To overcome current obstacles in NK cell‐based immunotherapies, we describe here a non‐viral lipid nanoparticle‐based delivery system that encapsulates small interfering RNAs (siRNAs) to gene silence the key intrinsic inhibitory NK cell molecules, SHP‐1, Cbl‐b, and c‐Cbl. The nanoparticles (NPs) target NK cells in vivo , silence inhibitory checkpoint signaling molecules, and unleash NK cell activity to eliminate tumors. Thus, the novel NP‐based system developed here may serve as a powerful tool for future NK cell‐based therapeutic approaches. Synopsis Natural Killer (NK) cells serve as a first line of immune defense against tumor growth and viral infections. This study demonstrates a nanobiology‐based drug delivery system to enhance NK cytotoxicity by suppressing intracellular inhibitory checkpoints in the tumor microenvironment (TME). NK cytotoxicity was enhanced by nano‐carriers encapsulating siRNAs that target the negative regulatory genes SHP‐1 and Cbls. Tumor growth was suppressed by these molecularly modified NK cells in‐vivo . Graphical Abstract Natural Killer (NK) cells serve as a first line of immune defense against tumor growth and viral infections. This study demonstrates a nanobiology‐based drug delivery system to enhance NK cytotoxicity by suppressing intracellular inhibitory checkpoints in the tumor microenvironment (TME).